1972
DOI: 10.1090/s0002-9939-1972-0289390-3
|View full text |Cite
|
Sign up to set email alerts
|

On elements with negative squares

Abstract: We prove that in a partially ordered linear algebra no element can have a square which is the negative of an order unit. In particular, the square of a real matrix cannot consist entirely of negative entries. We generalize the well-known theorem that the complex numbers admit no lattice order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…And in [6], DeMarr and Steger proved that if A is a finite-dimensional nontrivial algebra over R whose center contains a square root of −1, then A admits no partial order with respect to which it is a directed algebra over R. We first note that the proof of DeMarr and Steger may be easily generalized to prove the following result.…”
Section: Directed Algebrasmentioning
confidence: 94%
See 2 more Smart Citations
“…And in [6], DeMarr and Steger proved that if A is a finite-dimensional nontrivial algebra over R whose center contains a square root of −1, then A admits no partial order with respect to which it is a directed algebra over R. We first note that the proof of DeMarr and Steger may be easily generalized to prove the following result.…”
Section: Directed Algebrasmentioning
confidence: 94%
“…Let T be a totally ordered ring and recall (see [6]) that a directed T -algebra is an algebra D over T with a partial order that makes it a directed ring with the following compatibility property: if 0 τ ∈ T and 0 d ∈ D, then 0 τ d.…”
Section: Directed Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…In [1], Artin and Schreier observed that a totally ordered commutative field cannot have negative squares, and Johnson [7] and Fuchs [9] extended this result to totally ordered domains with unit element. In [12], Schwartz showed that an Archimedean lattice-ordered (commutative) field that has 1 > 0 and that is algebraic over its maximal totally ordered subfield cannot have negative squares, and in [13], DeMarr and Steger showed that in a partially ordered finite dimensional real linear algebra no square can be the negative of a strong unit. Furthermore, in [15], we guarantee the existence of directed commutative fields with negative squares.…”
Section: Introductionmentioning
confidence: 99%
“…(Note that DeMarr and Steger [3], have shown that C cannot be made into a directed algebra over the reals. )…”
mentioning
confidence: 99%